GESTIÓN DEL CAMBIO Y EL DESEMPEÑO LABORAL EN LOS TRABAJADORES I.E. SAN LUIS GONZAGA DE ICA. 2016 - ESPINO BALDIÑO, JOSE VLADIMIR (2016)
The present work of this research was to determine what relationship exists between change management and job performance in I.E. San Luis Gonzaga of Ica, 2016. To carry out this work, it was necessary to work on the methodological part with a hypothetical deductive model, of a basic type and non-experimental, descriptive correlational design, with a population of 190 workers from the San Luis Gonzaga de Ica Educational Institution, 2016, and that through a finite formula we worked with a sample of 114 workers. For data collection, the survey technique and two questionnaires had to be used as an instrument for each variable for its corresponding measurement, which is the Change Management variable, which consists of 40 items and 05 dimensions, among which are refer to the assessment, communication, knowledge, motivation and leadership and the other variable of job performance, of 34 items with 04 dimensions referring to productivity, teamwork, work under pressure and personal values. The results obtained from this research showed that there is no significant relationship between the change management variables and the work performance of the staff working at the San Luis Gonzaga Educational Institution in Ica, 2016. We can analyze that the non-parametric correlation coefficient of Spearman's Rho (0.48) is in relation to a moderate positive, between the change management variables and job performance, obtaining a bilateral significance level of p = 0.610 ≥ 0 , 05, which is far from the allowed value, therefore this indicates that “there is no significant relationship between change management and job performance in the workers of the San Luis Gonzaga educational institution in Ica. 2016. Keywords: Change management, job performance, assessment, communication, leadership, knowledge, motivation